Novel information about the bioactive compound profile, antioxidant and antiproliferative potential of Parkinsonia praecox (Fabaceae) - López-Romero, Julio Cesár; Torres-Moreno, Heriberto; Valencia-Rivera, Dora Edith; Leyva-Peralta, Mario Alberto; Lugo-Sepúlveda, Ramón Efraín; Robles-Zepeda, Ramón Enrique; Rodríguez-Martínez, Karen Lillian; Villegas-Ochoa, Mónica Alejandra; Salazar-López, Norma Julieta; González-Aguilar, Gustavo Adolfo (Instituto de Ecología, A.C., 2022)
Background and Aims: Parkinsonia praecox,“palo brea”, is a medicinal plant distributed in the Mexican Sonoran Desert. However, there is little information about the chemical composition and biological potential of this plant. As a consequence, the objective of the present study was to determine the chemical composition, as well as the antioxidant and antiproliferative activity, of P. praecox. Methods: Methanolic extracts of stems (PPS), berries (PPB) and flowers (PPF) were performed. Chemical composition was determined by phytochemical screening, Folin Ciocalteu and UPLC-DAD methods. Antioxidant activity was determined by DPPH, ABTS, ORAC and FRAP methods. Antiproliferative activity was evaluated by MTT against A549 (non-small-cell lung cancer cells), MDA-MB-231 (triple negative breast cancer), PC-3 (adenocarcinoma prostate cancer grade IV), HeLa (human cervical cancer) and L929 (non-cancerous subcutaneous connective tissue) cell lines. Results: Phytochemical screening showed the presence of terpenes, phenolic compounds, flavonoids, tannins and sugars in the extracts. PPS showed the highest (p<0.05) concentration of phenolic compounds (65.5 mg GAE/g), identifying and quantifying quercetin (218.86 µg/g). Additionally, PPS exhibited the highest capacity (p<0.05) to stabilize the DPPH (IC50: 137 µg/ml), ABTS (39.56 µM TE/g), hydroxyl radicals (ORAC: 1777.78 µM TE/g), and to reduce metals (FRAP: 935.6 µM Fe(II)/g). Similar behavior was observed in antiproliferative activity, since PPS presented the highest cytotoxicity (p<0.05): A549 (IC50: 341.3 µg/ml), MDA-MB-231 (IC50: 147.3 µg/ml), PC-3 (IC50: 78.8 µg/ml), HeLa (IC50: 121.6 µg/ml) and L929 (IC50: 93.29 µg/ml). Conclusion: This is the first research where the bioactive compound profile and the biological potential of P. praecox are reported. The results show the strong association between the antioxidant and the antiproliferative activities with the presence of phenolic compounds. This represents a potential support for the development of pharmacological therapies.